Potencial turístico de Matelândia/Pr: mapeamento e segmentação como base para políticas públicas - Stella, Fabiane Morello (2025)
This dissertation aimed to map the segmentation of the tourism offer and classify the tourist attractions of Matelândia, aiming to provide subsidies for the formulation of effective public policies for the development of local tourism. The research adopted an exploratory and descriptive approach, allowing to identify the relationship between the right to leisure and tourism as a driving factor of economic and social development. The study revealed that Matelândia has a significant tourism potential, especially in the segments of rural tourism, ecotourism, adventure tourism, gastronomic tourism and religious tourism. However, the lack of a systematic study on the attractions of the municipality makes it difficult to implement targeted strategies to strengthen tourism activity. The research highlighted the importance of regionalizing tourism as a planning tool, using the successful case of cycling tourism promoted by Adetur Cataratas e Caminhos as a reference for future actions. The main public policy proposals include the creation of a municipal tourism plan, the qualification of the workforce, the improvement of infrastructure for access to tourist attractions, the granting of tax incentives and the strengthening of tourism promotion through digital marketing strategies. These measures are essential to increase the attractiveness of the municipality, encourage investment in the sector and ensure sustainable growth of the activity. Given the findings, it is concluded that Matelândia has favorable conditions to consolidate itself as a regionally relevant tourist destination. However, for tourism to become an effective vector for economic and social development, coordination between public authorities, private initiative and the local community is essential in the management and implementation of structured and continuous policies.